Handlungsfelder von Stadt-Umland-Kooperationen für eine Energieversorgung mit erneuerbaren Energien. - Lentzen, Linda; Stablo, Järmo; Ruppert-Winkel, Chantal (oekom, 2016)
Viele Kommunen in Deutschland verfolgen das Ziel, ihre Energieversorgung vollständig auf erneuerbare Energien umzustellen. Stadt-Umland-Kooperationen bieten hierfür substanzielle Potenziale. Elf Handlungsfelder, die vor allem die Steuerung der Kooperationen sowie die Vernetzung und Einbindung von Akteuren betreffen, sind besonders relevant.

Urban-rural cooperations (URC) play an Important role in the success of Implementing a regional energy system based on renewable energy sources. A significant reason for this is that cities are seldom able to cover their energy needs with renewables alone. URC offer various opportunities for enabling such regional energy transition processes. Drawing on the concept of regional governance, this article aims to systematically outline different action areas for URC that are important for regional energy transition processes, and to demonstrate the concrete potentials of URC in these areas. Based on document analysis, expert interviews and three German case studies, we have identified eleven relevant action areas for the governance of URC in reaching energy goals as well as connecting and integrating different actors. The results can be used by municipalities to determine whether a URC can facilitate the energy transition processes in their specific context.
Urban-rural cooperations for energy transitions toward renewable energies : action areas.
Keywords: Energie; Energieversorgung; Stadtumland; Stadt-Land-Beziehungen; Kooperation; Erneuerbare Energie; Energiewende; Regional Governance; Masterplan